E- HEALTHCARE FOR PETS - Chou, Jing Haur (IRC, 2020)
This paper describes pet owner who need to consult veterinarian faced difficulty because unable to locate for veterinary services nearby which can provide them for consultation. However, there is no healthcare system to make the medical services for pets robust. The main achievements of the system were to be able: 1) study the existing current healthcare system for pets in the market with the experts; 2) developing an ehealthcare system to help pet owner to consult veterinarians of their pets at any time and allow pet owner to locate for nearby veterinary services; 3) carry out user acceptance test with pet owner and veterinarians to see the functionality of the system towards the healthcare for the pets. As a result, E-Healthcare for Pets has been proposed to construct a system where various pet owners requiring veterinary help at their home can consult veterinary, identify ideal veterinary services, locate nearby veterinary services and schedule request with veterinary. The system will demonstrate accommodating critical cases that do not reach veterinary clinic, for crisis cases that do not have veterinarian nearby, during late night emergencies and furthermore for preliminary assessment of pets.